2012
DOI: 10.1038/ni.2247
|View full text |Cite
|
Sign up to set email alerts
|

Intrathymic programming of effector fates in three molecularly distinct γδ T cell subtypes

Abstract: γδ T cells function in the early phase of immune responses. Although innate γδ T cells have primarily been studied as one homogenous population, they can be functionally classified into effector subsets based on the production of signature cytokines, analogous to adaptive T helper subsets. Unlike adaptive T cells, however, γδ T effector function correlates with genomically encoded TCR chains, suggesting that clonal TCR selection is not the primary determinant of γδ effector differentiation. A high resolution t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
252
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(275 citation statements)
references
References 51 publications
20
252
3
Order By: Relevance
“…The identification of γδ T cells producing IL-17 and details pertaining to their development have emerged only recently (14,18,25). Indeed, others have described unique developmental differences between the Vγ2 + and Vγ4 + γδ T-cell subsets in the dermis, despite their similar transcriptional profiles and common ability to produce IL-17 (16) and have shown that Vγ2 + , but not Vγ4 + , γδ T cells can be derived from adult bone marrow (39)(40)(41). Here we describe, to our knowledge, the first instance of a cytokine system whose absence enhances γδ-17-cell development.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of γδ T cells producing IL-17 and details pertaining to their development have emerged only recently (14,18,25). Indeed, others have described unique developmental differences between the Vγ2 + and Vγ4 + γδ T-cell subsets in the dermis, despite their similar transcriptional profiles and common ability to produce IL-17 (16) and have shown that Vγ2 + , but not Vγ4 + , γδ T cells can be derived from adult bone marrow (39)(40)(41). Here we describe, to our knowledge, the first instance of a cytokine system whose absence enhances γδ-17-cell development.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, γδ-17 cells exhibit limited TCR use, restricted to Vγ2 and Vγ4 expression (16). Thus, to gain further insight into the dysregulation of γδ-17 development in the absence of IL-15 vs. the absence of IL-15Rα, we examined the CD44 lo/int IL-17 + γδ-17 precursor population for Vγ expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, interferon‐ γ (IFN‐ γ ) production is associated with V γ 1 + , V γ 5 + and V γ 7 + γδ T cells. Although overall gene expression patterns are similar between V γ 4 + and V γ 6 + subsets,34 each subset has distinct features (Fig. 1).…”
Section: γδ T‐cell Subsets and Their Developmentmentioning
confidence: 94%
“…2 cd T cells expressing different Vcs have different effects on the immune responses. 8 Recent studies revealed a correlation between TCR-Vc expression and functional differentiation, 9,10 thus emphasizing the biological significance of the cd TCR segregation in the mouse. Nevertheless, specific evidence concerned with IL-17 producing cd T cells suggests that, at least in this case, the correlation between cd TCR expression and function is merely coincidental-waves of cd T cells expressing certain TCRs coincide with a thymic environment that temporarily favors TH17 differentiation.…”
Section: The CD T-cell Receptorsmentioning
confidence: 99%